2003
DOI: 10.2337/diabetes.52.9.2221
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Function of the Muscle Glycogen-Targeting Subunit of Protein Phosphatase 1 (GM) in Human Muscle Cells Depends on the COOH-Terminal Region and Glycogen Content

Abstract: G M , the muscle-specific glycogen-targeting subunit of protein phosphatase 1 (PP1) targeted to the sarcoplasmic reticulum, was proposed to regulate recovery of glycogen in exercised muscle, whereas mutation truncation of its COOH-terminal domain is known to be associated with type 2 diabetes. Here, we demonstrate differential effects of G M overexpression in human muscle cells according to glycogen concentration. Adenovirus-mediated delivery of G M slightly activated glycogen synthase (GS) and inactivated gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 30 publications
5
18
2
Order By: Relevance
“…Finally, in mouse, G M (muscle glycogen-targeting subunit of protein phosphate 1) is important for maintaining glycogen storage and GS activity, likely because of the action of the associated phosphatase, protein phosphatase 1 (39,40). G M also seems to play an important role in the increase in GS activity after glycogen depletion in human muscle cells (41). Thus, G M -directed phosphatase activity may be an important regulator of GS phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in mouse, G M (muscle glycogen-targeting subunit of protein phosphate 1) is important for maintaining glycogen storage and GS activity, likely because of the action of the associated phosphatase, protein phosphatase 1 (39,40). G M also seems to play an important role in the increase in GS activity after glycogen depletion in human muscle cells (41). Thus, G M -directed phosphatase activity may be an important regulator of GS phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this interpretation, high glycogen content has been reported to decrease protein phosphatase-1 (PP-1) activity (39) and overexpression of PP-1 glycogen binding regulatory subunit G M /R GL or PTG in cultured human primary muscle cells increases glycogen content (23), whereas deletion of G M /R GL decreases glycogen content in mouse muscles (2,38). Genetic approaches are required to determine the phosphorylation sites of GS, which regulate glycogen accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a study demonstrated that the transmembrane domain of PLN interacts directly with the C-terminus of this subunit (76), raising the possibility that G M /R GL may also target PP1c to PLN, providing yet another layer of complexity and regulation. Interestingly, a truncation mutation in the region that binds to the SR in human G M /R GL has been shown to result in aberrant PP1 regulation, impaired glycogen synthase activity and diminished glycogen content in human carriers (77, 78), human muscle cells (79), and in a knock-in mouse model expressing this mutant (78). However, the effects of this mutant were not reported in the heart.…”
Section: Regulation Of Pp1 In the Sarcoplasmic Reticulummentioning
confidence: 99%